Evaluation of an enhanced scheme for high-level nested network mobility - Ali Mohammed, Mohammed Babiker; Hassan Abdalla Hashim, Aisha (IJCSNS, 2015)
Recently, wireless devices have been used significantly due to the continuous and enormous services that they provide. The Mobility Support has been designed to achieve a permanent and continuing access to the Internet while the wireless devices are roaming and changing their points of attachment. One of the major challenges that arise is how to achieve seamless mobility and high network performance. The Internet Engineering Task Force (IETF) has developed Mobile IP, which allows Mobile node to be connected while it is moving as well as functioning in foreign mobile network zone using its original IP address. IETF also in order to manage mobility of an entire network as single unit, they developed NEMO Basic Support Protocol (NEMO BS), which allows Mobile Routers to move and change their point of attachment. When a Mobile Router connected to other mobile router on foreign mobile network, it makes a hierarchical structure known as nested mobile network; nested mobile network suffers from deferent problems due its complexity structure. When the level of nesting becomes high, problems of tunneling overhead are increased, which will produce high message delay and affect network performance. Many proposed schemes have been introduced to overcome nested network mobility issues. However, novel efforts are required. This research aim to present and evaluate a new scheme to support nested network mobility especially in high level of nesting. The evaluation of this proposed scheme is done using analytical approach. The proposed scheme enhancement is benchmarked with NEMO protocol and ROTIO approach witch it based on IETF standers. The result obtained had shown that the proposed scheme has better performance than the benchmark.